(untitled) (Universal International Scientific Journal, 2026)
In this article, the problem of developing soft competencies of managerial personnel is analyzed based on modern pedagogical and management theories. The essence of soft competencies, the structure of their development, the main components, and their functional significance in management activities are scientifically and theoretically substantiated. The research results are of great importance in improving the system of training and advanced training of managerial personnel